Demonstration of the synergistic effect of biochar and Trichoderma harzianum on the development of Ralstonia solanacearum in eggplant - Ahmad, Chaudhry Ali; Akhter, Adnan; Haider, Muhammad Saleem; Abbas, Muhammad Taqqi; Hashem, Abeer; Avila-Quezada, Graciela Dolores; Abd_Allah, Elsayed Fathi (Frontiers in Microbiology, 2024)
Soil degradation has been accelerated by the use of chemical pesticides and poor agricultural practices, having impact on the crop productivity. Eco-friendly biochar application to enhance soil quality and sequester carbon, has recently gained a lot of significance in the field of sustainable agriculture. Thise study aimed to determine the individual and combined effects of Leaf Waste Biochar (LWB) and bio-control agent Trichoderma harzianum (BCA) on the development of bacterial wilt in eggplant (Solanum melongena) caused by Ralstonia solanacearum (RS). The effects of LWB and BCA on eggplant physiology and defense-related biochemistry were comprehensively examined. Inoculated (+RS) and un-inoculated (-RS) eggplants were grown in potting mixtures containing 3 and 6% (v/v) LWB, both in the presence and absence of BCA. Percentage disease index was considerably reduced (90%) in plants grown in 6% LWB+ BCA amended treatments. Moreover, the plants grown in LWB and inoculated with BCA had higher phenolics, flavonoids and peroxidases contents as compared to non-amended control. Combined effect of BCA and LWB induced an increase in level of bio-chemicals (total phenolics, flavonoids and peroxidases) were evident in plants showing resistance against bacterial wilt development particularly in biochar amended potting substrate. Moreover, the level of NPK was significantly increased (92.74% N, 76.47% P, 53.73% K) in the eggplants cultivated in 6% LWB + BCA composition. This study has shown that the association of T. harzianum with biochar improved the plant growth and reduced R. solanacearum induced wilt. Furthermore, the combined impact of biochar and T. harzianum was higher in terms of wilt suppression and increase in plant physiological measurements when the concentration of the biochar was 6%. Biochar along with bio-control agent triggered biochemical alterations, thus enhancing the management of disease-infested soils.